Childhood Abuse, Goal-Striving Stress and Self-Esteem: An Explanatory Role for Perceptions of Divine Control? - Upenieks, Laura (Journal of religion and health, 2023)
Early life course events and experiences affect lifelong processes of human development, and at the forefront of life course research, is how negative conditions during childhood compromise adult well-being. In the current study, we propose that individuals who experience early life adversity may be more susceptible to the effect of stressors that are also very much rooted in the self-concept, namely goal-striving stress, the feeling of falling short of one’s expectations. Using data from the 2014 Nashville Stress and Health Study from the United States (NSAHS), we examine this process and consider how elements of religiosity, particularly beliefs in God’s causal influence in human life (divine control) explain why goal-striving stress takes a larger toll on the self-esteem of individuals who experienced childhood abuse. Our findings indicate that (1) childhood abuse was positively associated with goal-striving stress and inversely associated with self-esteem, (2) goal-striving stress was inversely associated with self-esteem, (3) goal-striving stress exacerbated the association between childhood abuse and lower self-esteem. Mediated-moderation analyses also revealed that (4) lower perceptions of divine control explain why goal-striving stress was more damaging for victims of childhood abuse. Taken together, this study contributes to a growing body of work on anticipatory stressors and linkages to the self-concept for victims of early life adversity, and how adversity early in the life course might undermine key religious resources like divine control that may otherwise mitigate the noxious effects of stress.